Understanding slow-growing alumina scale mediated by reactive elements: Perspective via local metal-oxygen bonding strength. (June 2018) - Shang, Shun-Li; Wang, Yi; Gleeson, Brian; Liu, Zi-Kui
Abstract: Interatomic bonding strength/energy can be quantified by stretching force constants (SFC) after first-principles phonon calculations. Here, we show that the slow-growing alumina (α-Al2 O3 ) scale mediated by reactive elements (REs) can be understood via the strong REO bonding energy from the present SFC model applied to oxides (Al2 O3, Cr2 O3, Ti2 O3, ZrO2, HfO2, Y2 O3, and La2 O3 ), Al3 M, and Al47 MO72 (M = Cr, Ti, Zr, Hf, Y, and La). The present model indicates that Hf is the best RE in retarding alumina scale growth, agreeing with the analyses from bulk modulus, melting point, and enthalpy of formation of oxides, and experimental observations. Graphical abstract: Unlabelled Image